Pengembangan Instrumen Penilaian Sikap Disposisi Matematis Pada Materi FPB Dan KPK SD/MI Tunanetra - Ahmad Surohman (Al-Bidayah : jurnal pendidikan dasar Islam, 2019)
This research is a development research that aims to study the product development process of mathematical disposition instruments in FPB and KPK material at SDLB A Yaketunis Yogyakarta, second to find out the feasibility of instrument products, mathematical dispositions on FPB and KPK material in SDLB A Yaketunis Yogyakarta. The results of the research on developing instruments about mathematical dispositions in FPB and KPK material in SDLB A Yaketunis Yogyakarta are as follows: products related to reliable coordination in the joba test have been obtained 0.7 so that the data error is 30%. Then according to experts this product has been proven valid.